2000
DOI: 10.1002/1439-7633(20001117)1:4<262::aid-cbic262>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

The 6‐OH Group of D ‐Inositol 1‐Phosphate Serves as an H‐Bond Donor in the Catalytic Hydrolysis of the Phosphate Ester by Inositol Monophosphatase

Abstract: Inositol monophosphatase plays a pivotal role in the biosynthesis of secondary messengers and is believed to be a target for lithium therapy. It is established how a lithium ion works in inhibiting the enzyme but details of the mechanism for the direct magnesium ion activated hydrolysis of the substrate have been elusive. It is known that substrates require a minimal 1,2-diol phosphate structural motif, which in D-myo-inositol 1-phosphate relates to the fragment comprising the 1-phosphate ester and the 6-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…We have previously demonstrated that 6-alkylamino side chains are tolerated at the active site of IMPase; 6-amino-and 6-methylamino-phosphate derivatives having been shown to be substrates of IMPase. 15,20 Compound 6i is merely the potent inhibitor 3 without a phosphate group attached at C-1. It was hoped that since the phosphate group had been removed then the pendant arm of 3, above all others, would compensate for the binding energy that would be lost through this change.…”
Section: Synthesis Of Product-like Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that 6-alkylamino side chains are tolerated at the active site of IMPase; 6-amino-and 6-methylamino-phosphate derivatives having been shown to be substrates of IMPase. 15,20 Compound 6i is merely the potent inhibitor 3 without a phosphate group attached at C-1. It was hoped that since the phosphate group had been removed then the pendant arm of 3, above all others, would compensate for the binding energy that would be lost through this change.…”
Section: Synthesis Of Product-like Inhibitorsmentioning
confidence: 99%
“…[3][4][5][6][7][8] A water molecule associated with Mg 2ϩ 1 deep within the active site acts as a nucleophile and attacks the phosphate group of the substrate -inositol-1-phosphate (-Ins-1-P) 1 and a second water molecule, coordinated to Mg 2ϩ 2 and hydrogen bonded to the 6-OH group of 1 acts as a general acid, protonating the inositolate group as it leaves. 15 Deletion of this 6-OH group removes any substrate activity from related compounds and it is known that the 4-OH and 2-OH groups along with the 1-O atom provide strong interactions for the binding of the substrate to the active site. 16 Many mechanism-based inhibitors of IMPase have been synthesized and evaluated during the accumulation of the above knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the reaction energy profile (Figure ) suggests that the reaction starts with proton transfer from wat86 to a phosphonyl oxygen atom of Ins(1)P, followed by proton transfer to a carboxylate group of Glu70 and then to the MI oxyanion via a water molecule (wat184). This important role of wat184 in the catalysis was previously proposed by Miller et al and Gill et al The most favorable pathway in Figure involves a barrier of just 26 kcal/mol, which does not seem high enough to exclude the two-metal mechanism. Moreover, we have demonstrated above that no favorable pathway could be described for the three-metal mechanism.…”
Section: Resultsmentioning
confidence: 52%
“…Wilkie et al also ran MM energy minimization and MD simulation on IMPase and concluded that the reaction follows a noninline displacement mechanism that is accompanied by pseudorotation . A more recent MM study by the same group amended this conclusion and also suggested that a water molecule bound to the Mg 2+ ion at M2 serves as a proton donor . Fujita et al performed docking simulation on human IMPA2 in complex with Mg 2+ ions and Ins(1)P, and proposed that the dephosphorylation reaction proceeds with three Mg 2+ ions .…”
Section: Introductionmentioning
confidence: 99%
“…Site-selective group transfers to hydroxyl groups are relevant not only for the synthesis of functionalized alcohols but also for their deoxygenation. The removal of specific hydroxyl groups from 13 would allow for biological studies on the importance of the OH functionality at those particular positions. Toward this end, exchange of the simple acylating agents above for either a phosphoramidite or thiocarbonylating agent can set up radical-mediated cleavage of its corresponding derivatives (Figure ). Reaction conditions modeled after those of Koreeda were developed for phosphoramidite transfer in the absence of either hydrolysis or oxidation of the resulting P­(III) species .…”
Section: Group Transfer To Hydroxyl Groupsmentioning
confidence: 99%